Isolated lung nodule.: Importance of extemporaneous biopsy - Díaz, Luis Felipe; Xavier, Artigas (Cirugía del Uruguay, 1977)
A coin lesion was detected by radiology in a 38- year-old patient, presumptively diagnosed as neoplasm and operated on. The possibility of hydatid sequella was considered during the operation, a mistake corrected by extemporaneous biopsy which proved it to be an adenocarcinoma, thus showing the importance of this test. A right lower lobectomy was performed. Four months later the patient was asyntomatic. The papel includes a brief review of coin lesions.